Autophagy gene variant IRGM -261T contributes to protection from tuberculosis caused by Mycobacterium tuberculosis but not by M. africanum strains. - Christopher D Intemann (Public Library of Science (PLoS), 2009)
The human immunity-related GTPase M (IRGM) has been shown to be critically involved in regulating autophagy as a means of disposing cytosolic cellular structures and of reducing the growth of intracellular pathogens in vitro. This includes Mycobacterium tuberculosis, which is in agreement with findings indicating that M. tuberculosis translocates from the phagolysosome into the cytosol of infected cells, where it becomes exposed to autophagy. To test whether IRGM plays a role in human infection, we studied IRGM gene variants in 2010 patients with pulmonary tuberculosis (TB) and 2346 unaffected controls. Mycobacterial clades were classified by spoligotyping, IS6110 fingerprinting and genotyping of the pks1/15 deletion. The IRGM genotype -261TT was negatively associated with TB caused by M. tuberculosis (OR 0.66, CI 0.52-0.84, P(nominal) 0.0009, P(corrected) 0.0045) and not with TB caused by M. africanum or M. bovis (OR 0.95, CI 0.70-1.30. P 0.8). Further stratification for mycobacterial clades revealed that the protective effect applied only to M. tuberculosis strains with a damaged pks1/15 gene which is characteristic for the Euro-American (EUAM) subgroup of M. tuberculosis (OR 0.63, CI 0.49-0.81, P(nominal) 0.0004, P(corrected) 0.0019). Our results, including those of luciferase reporter gene assays with the IRGM variants -261C and -261T, suggest a role for IRGM and autophagy in protection of humans against natural infection with M. tuberculosis EUAM clades. Moreover, they support in vitro findings indicating that TB lineages capable of producing a distinct mycobacterial phenolic glycolipid that occurs exclusively in strains with an intact pks1/15 gene inhibit innate immune responses in which IRGM contributes to the control of autophagy. Finally, they raise the possibility that the increased frequency of the IRGM -261TT genotype may have contributed to the establishment of M. africanum as a pathogen in the West African population.